Molecular Marvels: Small Molecules Paving the Way for Enhanced Gene Therapy - Sebastian Hasselbeck; Xinlai Cheng (MDPI AG, 2023)
In the rapidly evolving landscape of genetic engineering, the advent of CRISPR-Cas technologies has catalyzed a paradigm shift, empowering scientists to manipulate the genetic code with unprecedented accuracy and efficiency. Despite the remarkable capabilities inherent to CRISPR-Cas systems, recent advancements have witnessed the integration of small molecules to augment their functionality, introducing new dimensions to the precision and versatility of gene editing applications. This review delves into the synergy between CRISPR-Cas technologies based specifically on Cas9 and small-molecule drugs, elucidating the pivotal role of chemicals in optimizing target specificity and editing efficiency. By examining a diverse array of applications, ranging from therapeutic interventions to agricultural advancements, we explore how the judicious use of chemicals enhances the precision of CRISPR-Cas9-mediated genetic modifications. In this review, we emphasize the significance of small-molecule drugs in fine-tuning the CRISPR-Cas9 machinery, which allows researchers to exert meticulous control over the editing process. We delve into the mechanisms through which these chemicals bolster target specificity, mitigate off-target effects, and contribute to the overall refinement of gene editing outcomes. Additionally, we discuss the potential of chemical integration in expanding the scope of CRISPR-Cas9 technologies, enabling tailored solutions for diverse genetic manipulation challenges. As CRISPR-Cas9 technologies continue to evolve, the integration of small-molecule drugs emerges as a crucial avenue for advancing the precision and applicability of gene editing techniques. This review not only synthesizes current knowledge but also highlights future prospects, paving the way for a deeper understanding of the synergistic interplay between CRISPR-Cas9 systems and chemical modulators in the pursuit of more controlled and efficient genetic modifications.